Women with dysmenorrhoea are hypersensitive to experimentally induced forearm ischaemia during painful menstruation and during the pain‐free follicular phase. (15th October 2014) - Iacovides, S.; Avidon, I.; Baker, F.C.
Abstract Background Monthly primary dysmenorrhoeic pain is associated with increased sensitivity to painful stimuli, particularly in deep tissue. We investigated whether women with dysmenorrhoea, compared with controls, have increased sensitivity to experimentally induced deep‐tissue muscle ischaemia in a body area distant from that of referred menstrual pain. Methods The sub‐maximal effort tourniquet test was used to induce forearm ischaemia in 11 women with severe dysmenorrhoea and in nine control women both during menstruation and in the follicular phase of the menstrual cycle. Von Frey hair assessments confirmed the presence of experimental ischaemia. Women rated the intensity of menstrual and ischaemic pain on a 100‐mm visual analogue scale. Results Women with dysmenorrhoea [mean (SD): 68 (20) mm] reported significantly greater menstrual pain compared with controls [mean (SD): 2 (6) mm; p = 0.0001] during the menstruation phase. They also rated their forearm ischaemic pain as significantly greater than the controls during the menstruation [dysmenorrhoeics vs. controls mean (SD): 58 (19) mm vs. 31 (21) mm, p < 0.01] and follicular [dysmenorrhoeics vs. controls mean (SD): 60 (18) mm vs. 40 (14) mm, p < 0.01] phases of the menstrual cycle. Conclusions These data show that compared with controls, women who experience severe recurrent dysmenorrhoea have deep‐tissue hyperalgesia to ischaemic pain in muscles outside of the referred area of menstrual pain both during the painful menstruation phase and pain‐free follicular phase. These findings suggest the presence of long‐lasting changes in muscle pain sensitivity in women with dysmenorrhoea. Our findings that dysmenorrhoeic women are hyperalgesic to a clinically relevant, deep‐muscle ischaemic pain in areas outside of referred menstrual pain confirm other studies showing long‐lasting changes in pain sensitivity outside of the painful period during menstruation.